Stepwise isolation of low-valent, low-coordinate Sn and Pb mono- and dications in the coordination sphere of platinum - Braunschweig, Holger; Celik, Mehmet Ali; Dewhurst, Rian D.; Heid, Magdalena; Hupp, Florian; Sen, Sakya S. (Chemical Science, 2015)
Synthetic access to low-coordinate Pb mono- and dications is in general impeded due to their poor solubility and highly electrophilic nature. However, the electrophilicity of these cations can be tamed by attaching them to electron-rich transition metals. Following this principle we have isolated low-valent Pb mono- ([(Cy3P)(2)Pt-PbCl](2)[AlCl4](2), 8a) and dications ([(Cy3P)(2)Pt(Pb)][AlCl4](2), 11) in the coordination sphere of platinum. The same approach then has been implemented for the isolation of analogous low-valent Sn mono- (7a) and dications (10). An energy decomposition analysis (EDA-NOCV) was performed to investigate the nature of Pt-Pb and Pb-Cl bonding in [(Cy3P)(2)Pt(PbCl2)] (2), 8a and 11. The results show that the Pt-Pb bonds in 8a and 11 are electron-sharing in nature, whereas that of the precursor 2 is a dative bond. The breakdown of attractive interactions in 2, 8a and 11 reveals that the ionic interactions in the analyzed Pt-Pb and Pb-Cl bonds are always stronger than the covalent interactions, except for the Pb-Cl bond in 8a. The calculated D3 dispersion energies show that dispersion interactions play a key role in the thermodynamic stability of 2, 8a and 11.